Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Pada Kurikulum Merdeka Di MAN 2 Palembang - Ibrahim Ibrahim; Devi Rahma; Tri Wulandari; Rafa Nabila; Cahyadi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research discusses the Implementation of the Strengthening Project for the Student Profile of Pancasila (P5) in the Independent Curriculum at MAN 2 Palembang. The purpose of this study is to analyze the impact on students regarding the implementation of the Pancasila Student Profile Strengthening Project (P5) at MAN 2 Palembang. The research is qualitative, with a descriptive approach. Interviews were conducted with individuals representing the criteria of MAN 2 Palembang to gather data. The 10th-grade class is the only class at MAN 2 Palembang participating in the Pancasila student profile enhancement project. As part of their independent study, students develop and implement a project. One of the independent curriculum project activities is the implementation of P5 activities. The P5 project at MAN 2 Palembang consists of three parts: a presentation by the class teacher on traditional South Sumatra cuisine and related topics (recipes passed down from generation to generation), a session on the socialization of the impact of bullying and drug use in the school auditorium, and a student performance showcasing traditional South Sumatra cuisine in the school auditorium.